A grammatical error analysis in writing among the second semester students of management department of STIE SBI - Bonifasia Ekta Fima Natalia (Universitas Sarjanawiyata Tamansiswa, 2020)
This research aims at describing the grammatical errors that happen in the final assignment of second-semester students of Management Department of STIE SBI. Two research questions are formulated in this study. They are (1) What are grammatical errors in writing made by second-semester students of Management Department of STIE SBI? and (2) What are the possible causes or sources of those errors? The research study is classified into a descriptive study. The data source was collected from the students’ writing of the second semester. The key instrument used in this research is the researcher and writing result. The researcher used Dulay’s, Burt, and Krashen theory in analyzing the data. As the supplementary tools of the instruments, some forms of data sheets were used during the research analysis. There were two kinds of data: quantitative and qualitative. The quantitative data were presented in the form of frequency charts for each category of surface strategy taxonomy and comparative analysis. Then, the qualitative data described each category that occurred in the students’ writing. The researcher described the situation about the occurrence of the errors in the students’ writing. Based on the analysis of the grammatical errors, four types of errors were found. The most frequent error was committed in misformation (47.01%). The second highest frequency of error occurrence was an addition (29.61%). The third percentage of grammatical error in writing was an omission which was 176 times of occurrence (21.89%). The least percentage of students’ error was misordering. The students only committed 12 errors (1.49%) in their writing. Based on the result, it is figured out that the students still have difficulties in learning grammatical structures in the writing process.